Performance evaluation of enhanced pulse width modulation techniques for cascaded multilevel inverter - Jayaprakasam Vinothini; Ramkumar Ravindran (Bulletin of Electrical Engineering and Informatics, 2026)
The nine-level multi-level inverter (MLI) uses a DC voltage supply, seven switches, four capacitors, and twelve diodes to generate an AC output with nine distinct voltage levels. Control strategies like pulse width modulation (PWM), fuzzy logic control (FLC), and time ratio control (TRC) regulate the inverter’s performance. Multi-carrier PWM techniques such as APOD, POD, PD, and multi-reference PWM are applied for precise control. The system is simulated in MATLAB, and performance is evaluated based on output voltage RMS and total harmonic distortion (THD), ensuring compliance with IEEE standards. FLC and TRC have been proposed as control approaches for the mighty nine-level MLI. The proposed inverter uses 60% fewer components than traditional designs while giving better power quality. All methods performed better than existing field-programmable gate array (FPGA)-based systems that had 19.86% THD. The performance evaluation includes output voltage rms and THD indices, requirements that must meet IEEE standards. The proposed strategies are compared with existing techniques in the literature.